Term Pluralisme Agama dalam Al-Qur’an: (Pendekatan Interdipliner Tafsir Tematik dan Ilmu Pendidikan) - Muhammad Ahsanul Aziz; Kusnadi; Aristhopan Firdaus (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Religious pluralism is a contemporary issue that continues to be debated, especially in Islamic discourse, because it is often perceived as contradictory to the teachings of the Qur'an. However, the Qur'an substantively contains values ​​of diversity, tolerance, and social justice that align with the principles of pluralism. This article aims to analyze Qur'anic terms that represent the values ​​of religious pluralism and examine their implications from an Islamic educational perspective. This research uses a qualitative method with a content analysis model through library research. The approach used is interdisciplinary, integrating thematic interpretations of the Qur'an with Islamic educational science. The results show that although the term pluralism is not explicitly mentioned in the Qur'an, its substance is reflected in several principles of Islamic teachings, such as tasamuh (tolerance), tawazun (balance), tawasuth (moderation), ta'adul/i'tidal (justice), and ta'awun (cooperation). These values ​​have strategic relevance in Islamic education as a pedagogical foundation for developing students with morals, tolerance, and the ability to live harmoniously in a pluralistic society. This research has implications for strengthening the paradigm of Islamic education that emphasizes the exclusivity of faith and social inclusivity as a constructive response to the reality of religious diversity.